SOSIALISASI PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI RW 12 KELURAHAN TANGKERANG SELATAN - Bobi Handoko; Sherly Mutiara; Yoti Sri Haryani; Dwi Suci Asriani (Awal Bros Journal of Community Development, 2023)
Dengue Hemorrhagic Fever (DHF) is still a disease that is feared especially in the tropical countries including Indonesia. Continuous efforts are needed in terms of preventing dengue hemorrhagic fever. The purpose of this activity is to provide an explanation of various ways to prevent dengue hemorrhagic fever and at the same time provide an opportunity for public to act as ambassadors for the environment. The method of this activity is in the form of community socialization. This socialization was considered quite successful, seen from the enthusiasm of the participants in asking questions about DHF. It can be concluded that this outreach activity is very useful in increasing knowledge and community participation in the prevention of dengue hemorrhagic fever.